ALKALINE PROTEASE, AMYLASE AND CELLULASE ACTIVITIES OF YELLOW RASBORA, Rasbora lateristriataBlkr., AT DIFFERENT FEEDING LEVELS - Untung Susilo; Purnama Sukardi; Ridwan Affandi (Universitas Jenderal Soedirman, 2016)
Alkaline proteases, amylase and cellulase activities of digestive organ of yellow rasbora, Rasbora lateristriata Blkr., was evaluated with four different feeding levels of 0.34g protein+0.03g fiber, 1.01g protein+0.10g fiber, 1.69g protein+0.16g fiber and 2.36g protein+0.23g fiber/day/100 g fish biomass. A total of 280 fish with average body weight of 0.71±0.06g were used in this study. The results showed that the difference in the feeding levels resulted in a significant difference in trypsin and chymotrypsin activities (P <. 05), but not for amylase and cellulase activities (P > .05). In conclusion, protein digestion capacity increased, but not to the digestion of starch and fiber in response to different feeding levels and the optimal feeding level for yellow rasbora was 1,01g protein+0,10g fiber/day/100 g fish biomass.